Where do prices come from? Sociological approaches to price formation - Jens Beckert (Max Planck Institute for the Study of Societies, 2011)
The article provides an overview of the state of the art of sociological research on price formation. The dominant trait of the sociological approach to prices is to understand price formation not as the outcome of individual preferences but as the result of the social and political forces operating within the market field. The article proceeds from the concept of market fields and is organized around the three dominant approaches in economic sociology: the network approach, the institutional approach, and the cultural approach. – – Der Artikel gibt einen Überblick über den Forschungsstand zum Thema Preisbildung in der Soziologie. Ausgangspunkt der Betrachtung von Preisen aus soziologischer Perspektive ist, diese nicht als das Resultat individueller Präferenzen zu verstehen, sondern als Ausdruck der sozialen und politischen Kräfte in Märkten. Der Artikel orientiert sich an dem Konzept der Marktfelder und ist anhand der drei Hauptrichtungen der Wirtschaftssoziologie strukturiert: des Netzwerkansatzes, des institutionellen Ansatzes und des kulturellen Ansatzes.
Keywords: 300